A dynamic view of technology acquisition. (1st January 2001) - Macdonald, Stuart; James, Andrew
Until very recently, GKN had but two core businesses, each with its own core technology. In both cases, the business had been built around technologies obtained externally - one through joint venture, the other by acquisition. In neither case, though, did the most senior management in GKN attach any particular importance to the technology the company was acquiring, many years passing before its significance began to seep through. These core businesses now provide most of GKN's profit. The case study shows the limitations of the static perspective normally adopted in the study of acquisition. Such a perspective focuses on the stock of resources and on how these may complement those of the acquirer. It pays less attention to what might develop in time, to the flow of resources. It seems to assume two separate tasks the mixing of two technologies followed by the development of the joint technology, the first to be accomplished to establish a new stock of resources before the second, the management of their flow, can be undertaken. This traditional approach may not be entirely appropriate to the study of acquisition in which technology is a major resource. A more dynamic approach in keeping with attitudes towards the management of technology is required both from managers and from those who study their behaviour.